Pitch strength of normal and dysphonic voices - Shrivastav, Rahul (Acoustical Society of America, 2012)
Two sounds with the same pitch may vary from each other based on saliency of their pitch sensation. This perceptual attribute is called “pitch strength.” The study of voice pitch strength may be important in quantifying of normal and pathological qualities. The present study investigated how pitch strength varies across normal and dysphonic voices. A set of voices (vowel /a/) selected from the Kay Elemetrics Disordered Voice Database served as the stimuli. These stimuli demonstrated a wide range of voice quality. Ten listeners judged the pitch strength of these stimuli in an anchored magnitude estimation task. On a given trial, listeners heard three different stimuli. The first stimulus represented very low pitch strength (wide-band noise), the second stimulus consisted of the target voice and the third stimulus represented very high pitch strength (pure tone). Listeners estimated pitch strength of the target voice by positioning a continuous slider labeled with values between 0 and 1, reflecting the two anchor stimuli. Results revealed that listeners can judge pitch strength reliably in dysphonic voices. Moderate to high correlations with perceptual judgments of voice quality suggest that pitch strength may contribute to voice quality judgments.